STRATEGI KEMENTERIAN PARIWISATA DAN EKONOMI KREATIF PERIODE 2019-2024 DALAM MENINGKATKAN CITRA INDONESIA SEBAGAI NEGERI REMPAH - Salma Destiviani, Tri; Azmawati, Dian (UIN Alauddin Makassar, 2025)
This research aims to analyze the strategies of the Ministry of Tourism and Creative Economy (Kemenparekraf) during the 2019-2024 period in enhancing Indonesia's image as the